Strategi Guru Aqidah Akhlak dalam Mengembangkan Karakter Religius Siswa - Putri, Nabila Syafinka; Setiawan, Hasrian Rudi; Pohan, Selamat (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to analyze the strategies of Aqidah Akhlak teachers in instilling religious values, the implementation of steps to form religious character, as well as supporting and inhibiting factors at MTs PAB 1 Helvetia. The study used a qualitative descriptive method. The results show the teachers' implementation of habituation, role modelling, and reinforcement strategies through routine activities such as prayer, tadarus, yasinan, and congregational prayer. The implementation is carried out through continuous guidance, supervision, and evaluation. Supporting factors include madrasah culture, teacher commitment, facilities, and parental support, while obstacles include differences in student discipline, limited family support, a less conducive external environment, and challenging classroom supervision. Teacher strategies play an important role in shaping students' religious character.